Study on the relationship between work value and job satisfaction of university teachers in Henan Province, China - Zhang , Qian; Yeh, Juo-Lan, (Journal of Roi Kaensarn Academi, 2023)
Since the work value orientation theory, researchers at home and abroad mainly to professional position of staff, administrative assistant, soho, private employees, government workers, and primary and secondary school teachers and special education teachers as the research object, and around the concept of work value orientation definition, structure measurement, influence factors and its influence to carry out the research. However, throughout the existing literature, the research object, and the relevant research based on the perspective of work value orientation is still insufficient. As the specific workers, the work content and achievements of college teachers have a very important influence on the national talent training. So this study in China Henan university teachers as a research object, the questionnaire method, exploratory factor, confirmatory factor, clustering and related analysis method, to explore the type of university teachers work value orientation, and the relationship between different work value orientation and job satisfaction, and put forward the university teachers management countermeasures and Suggestions, so as to improve the university teachers' job satisfaction and job sense.